Brain-Computer Interfaces for upper limb motor rehabilitation of stroke patients - Cariño-Escobar, R. I.; Cantillo-Negrete, J. (Revista Mexicana de Ingenieria Biomedica, 2020)
Brain-Computer Interfaces (BCI) decode users’ intentions from the central nervous system and could be applied for upper limb motor rehabilitation of patients that have suffered stroke, one of the main causes of disability worldwide. Despite that research groups have reported the efficacy of these systems, a consensus has not yet been reached regarding their true potential. For this reason, a review of up-to-date assessments of BCI for upper limb stroke rehabilitation is presented from the perspective of analyzing common and different design variables presented across studies. Clinical and pilot studies with a control group were included in the review. Most BCI interventions assessments were performed with robotic assistive devices as feedback, followed by neuromuscular electrical stimulation (NMES) and visual feedbacks. Compared to other experimental interventions, the effects of a BCI intervention have been reported in a low number of patients. In addition, high variability between studies’ designs such as stroke etiology and interventions’ duration, do not allow to assess the potential of BCI for stroke rehabilitation. However, a trend towards significant rehabilitation outcomes with BCI systems can be highlighted, encouraging research groups to better coordinate in order to make valuable contributions to the field.